2016
DOI: 10.3892/mmr.2016.5933
|View full text |Cite
|
Sign up to set email alerts
|

Selection of suitable reference genes for gene expression studies in normal human ovarian tissues, borderline ovarian tumours and ovarian cancer

Abstract: The use of reference genes is the most common method of controlling the variation in mRNA expression during quantitative polymerase chain reaction, although the use of traditional reference genes, such as β‑actin, glyceraldehyde‑3‑phosphate dehydrogenase or 18S ribosomal RNA, without validation occasionally leads to unreliable results. Therefore, the present study aimed to evaluate a set of five commonly used reference genes to determine the most suitable for gene expression studies in normal ovarian tissues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Five commonly used reference genes were selected: actin beta (ACTB), beta-2-microglobulin (B2M), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), hypoxanthine phosphoribosyltransferase 1 (HPRT1), and TATA-box binding protein (TBP) (Santin et al, 2013;Weber et al, 2014;Iser et al, 2015;Ofinran et al, 2016;Wang et al, 2016a). RT-qPCR was performed using StepOnePlus Real-Time PCR cycler.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…Five commonly used reference genes were selected: actin beta (ACTB), beta-2-microglobulin (B2M), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), hypoxanthine phosphoribosyltransferase 1 (HPRT1), and TATA-box binding protein (TBP) (Santin et al, 2013;Weber et al, 2014;Iser et al, 2015;Ofinran et al, 2016;Wang et al, 2016a). RT-qPCR was performed using StepOnePlus Real-Time PCR cycler.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…The widely used ribosomal RNA (18S or 28S rRNA), for example, is not the most appropriate gene mainly because its expression is much higher and its degradation inferior to those of the target mRNA, the rRNA:mRNA ratio is highly variable between different samples, and its transcription pathway is independent of that of mRNA [21][22][23]. Furthermore, the selection of a reference gene based only on a literature search is equally inadequate, because the expression levels of several constitutive genes, such as GAPDH and ACTB, is known to vary considerably in the same tissue when tested under different experimental conditions [24][25][26]. Thus, previous reference gene validation is essential for each tissue and study, based on a set of candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, GAPDH and βactin were always selected as potential candidate reference genes, based on previous experience. However, previous studies have shown that the expression levels of these housekeeping genes (HKGs) can vary between cell types [6][7][8] and in different experimental conditions. 9,10 Therefore, prior to their initial use, the stability of the expression of certain HKGs should be validated first.…”
Section: Introductionmentioning
confidence: 99%